2022
DOI: 10.3389/fphar.2022.933998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc versus vitamin A supplementation on pediatric patients with community-acquired pneumonia

Abstract: Background: Community-acquired pneumonia (CAP) is one of the most common infectious diseases affecting the respiratory tract and is responsible for a high mortality rate in children less than 5 years of age. The mortality rate due to CAP is much higher in low/middle-income countries than in high-income countries due to malnutrition and different micronutrient deficiencies that weaken the immune system.Aim: The aim of this study was to compare the effects of zinc and vitamin A, as two elements of micronutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 53 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…[33][34][35] The relationship between vitamin D and zinc (Zn) levels and pneumonia was investigated, and it was revealed that vitamin and mineral deficiencies predispose to pneumonia. 36,37 In our study, we demonstrated a negative relationship between the income level of the family and the intake of nutritional support. Again, we detected a negative relationship between education level and vitamin D levels and a negative relationship between Zn levels in patients with cardiovascular system disease.…”
Section: Discussionsupporting
confidence: 48%
“…[33][34][35] The relationship between vitamin D and zinc (Zn) levels and pneumonia was investigated, and it was revealed that vitamin and mineral deficiencies predispose to pneumonia. 36,37 In our study, we demonstrated a negative relationship between the income level of the family and the intake of nutritional support. Again, we detected a negative relationship between education level and vitamin D levels and a negative relationship between Zn levels in patients with cardiovascular system disease.…”
Section: Discussionsupporting
confidence: 48%
“…Two RCTs on vitamin A supplementation reported divergent results. Enteral vitamin A supplementation reduced the length of hospital stay and pneumonic effusion in critically ill children with community-acquired pneumonia, but intramuscular vitamin A supplementation was not beneficial to critically ill septic adults [32,36].…”
Section: Vitamin Amentioning
confidence: 93%
“…There were no benefits in neurocritical patients, whereas a mortality benefit was shown in septic patients with AKI [30,31]. In addition, zinc supplementation in critically ill children with community-acquired pneumonia significantly shortened hospital length of stay and duration of pneumonic effusion [32].…”
Section: Zincmentioning
confidence: 97%
“…The potential use of nutritional treatments as additional therapy to improve recovery and lessen the severity of pneumonia in pediatric patients has drawn interest. Zinc and vitamin A are two micronutrients that have come to light as viable options with immunomodulatory qualities that may influence the development of pediatric CAP [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%